E-cadherin and loss of heterozygosity at chromosome 16 in breast carcinogenesis: different genetic pathways in ductal and lobular breast cancer? - Cleton-Jansen, Anne-Marie (BioMed Central, 2002)
Loss of heterozygosity at the long arm of chromosome 16 is one of the most frequent genetic events in breast cancer. In the search for tumour suppressor genes that are the target of loss of heterozygosity at 16q, the E-cadherin gene CDH1 was unveiled by the identification of truncating mutations in the retained copy. However, only lobular tumours showed E-cadherin mutations. Whereas investigations are still devoted to finding the target genes in the more frequent ductal breast cancers, other studies suspect the E-cadherin gene to also be the target in this tumour type. The present article discusses the plausibility of those two lines of thought.